Activation and employment support policies in OECD countries: An overview of current approaches - Herwig Immervoll; Stefano Scarpetta (IZA Journal of Labor Policy, 2012)
This note examines the balance of activation strategies in OECD countries, where this type of policy approach has a long tradition. Countries share the objective of strengthening employment and reducing benefit dependency and vulnerability among the working-age population, but the balance of policy measures differs widely. While debates on the effectiveness of active labour market policies have tended to focus on individual policy measures, this paper emphasizes the links between policy areas. We argue that an effective policy strategy rests on a finely tuned balance between income support, work incentives, as well as mutual obligations and active labour market programmes.
Keywords: H31; H53; J08; J68; 330; Arbeitsmarktpolitik; Systemvergleich; OECD-Staaten